Reverberation time of Wrocław Opera House after restoration - Rudno-Rudziński, Krzysztof; Dziechciński, P. (Archives of Acoustics, 2006)
One of the main acoustic goals set prior to restoration work on the Wrocław Opera Housein 1997 was to increase the auditorium’s reverberation time. Now, after the completion ofthe restoration work, comprehensive acoustic investigations of the Opera House, includingreverberation time, were carried out. Measurements were performed in accordance with theISO 3382.The reverberation time measurement results were analysed with regard to the absorptioncoefficient of seats. After the seats were installed, the effect of acoustic coupling with the stageand also the position of the orchestra pit’s movable floor was investigated.The effect of the location of a sound source (on the stage and in the open and covered partof the orchestra pit) on reverberation time was examined. The differences in reverberationtime between the measurement locations were compared with the differences in reverberationtime between the sound source locations.The current and pre-restoration reverberation time values were compared. It was found thatthe acoustic goal set for the restoration of the Opera House was achieved.